A Measurement Invariance Investigation of the Polish Version of the Dual Filial-Piety Scale (DFPS-PL): Student-Employee and Gender Differences in Filial Beliefs - Różycka-Tran, Joanna; Jurek, Paweł; Olech, Michał; Dmochowski, Tadeusz (Frontiers in Psychology, 2021)
Filial beliefs are defined as a cognitive script or even a contextualized personality construct for social exchanges, which shapes the attitudes of individuals. In the given study, we investigate the factorial structure of the Polish version of the Dual Filial Piety Scale (DFPS-PL) and verify whether measurement of filial piety is invariant among students and employees, and among men and women. Two studies were conducted on different age samples: 489 students aged 18–24 and 849 employees aged 25–64. In order to verify the hypotheses, the DFPS-PL was administered. As a result of confirmatory factor analyses (CFA), it has been demonstrated that the structure of filial piety measured by the DFPS-PL among students and employees, and men and women, could be interpreted as two-factorial, and that there is partial scalar measurement invariance for the tested model across these groups (MGCFA). The comparison of the average latent mean scores suggests that employees declare a lower level of AFP (Authoritarian Filial Piety; need of social belonging and collective identity) than students. There were no significant differences between students and employees when RFP (Reciprocal Filial Piety; need of interpersonal relatedness) was compared. In addition, the results showed that women score higher in RFP than men. The given findings are discussed in the context of values transition in non-Asian countries. The main contribution is to confirm the factorial structure of the DFPS-PL and introduce the novel Eastern concept of Filial Piety to Western culture.